Efektivitas Ekstrak Goji Berry (Lycium Barbarum L.) Terhadap Jumlah Sel Makrofag Pasca Pencabutan Gigi Pada Tikus Wistar (Rattus Norvegicus) - Shieny Lokanata; Dian Soraya Tanjung; Tiara Salsabila Putri; Wulan Sahara Bengi (Jurnal Ilmiah Global Education, 2026)
Tissue damage due to tooth extraction triggers an inflammatory response that involves the vital role of macrophage cells in the healing process. Considering the potential antioxidant and anti-inflammatory activities of Lycium barbarum L., this study aims to test the effectiveness of goji berry extract gel at concentrations of 15%, 30%, and 55% on the number of macrophage cells after tooth extraction in Wistar rats. This in vivo laboratory experimental study with a post-test only control group design used 30 Rattus norvegicus as samples. Subjects were divided into negative controls, positive controls (povidone iodine), and goji berry extract gel treatment groups given through topical application for 7 days. Histopathological observations with hematoxylin-eosin staining were carried out on days 1, 3, 5, and 7, then the data were analyzed using the Shapiro–Wilk test, One-way ANOVA, and Post Hoc LSD. The analysis showed no significant difference on day 1 (p>0.05). Significant differences (p<0.05) were identified on days 3 and 5, where the number of macrophages in the treatment group was lower than in the control group. The most optimal reduction was seen on day 7 at concentrations of 30% and 55%. Goji berry extract gel was proven to be effective in reducing the number of macrophages during wound healing after tooth extraction, especially at concentrations of 30% and 55%.